2022
DOI: 10.3389/fonc.2022.936145
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor antagonism downregulates ATP-binding cassette transporters contributing to improved drug efficacy against melanoma and hepatocarcinoma in vivo

Abstract: Knockdown of GH receptor (GHR) in melanoma cells in vitro downregulates ATP-binding cassette-containing (ABC) transporters and sensitizes them to anti-cancer drug treatments. Here we aimed to determine whether a GHR antagonist (GHRA) could control cancer growth by sensitizing tumors to therapy through downregulation of ABC transporters in vivo. We intradermally inoculated Fluc-B16-F10 mouse melanoma cells into GHA mice, transgenic for a GHR antagonist (GHRA), and observed a marked reduction in tumor size, mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In the present study, we observed a marked suppression of gemcitabine resistance in the presence of GHRAs. We have previously shown that GHR inhibition sensitizes melanoma cells to paclitaxel, as well as platinumbased antineoplastic drugs like cisplatin [64][65][66], and the pyrimidine analog fluorouracil (5-FU) (70). Therefore, based on our previous and current studies, GHRAs can potentially augment the current anti-PDAC chemotherapeutic combinations such as gemcitabine-paclitaxel, as well as FOLFIRINOX (combination of 5-FU, oxaliplatin, irinotecan, and folinic acid).…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, we observed a marked suppression of gemcitabine resistance in the presence of GHRAs. We have previously shown that GHR inhibition sensitizes melanoma cells to paclitaxel, as well as platinumbased antineoplastic drugs like cisplatin [64][65][66], and the pyrimidine analog fluorouracil (5-FU) (70). Therefore, based on our previous and current studies, GHRAs can potentially augment the current anti-PDAC chemotherapeutic combinations such as gemcitabine-paclitaxel, as well as FOLFIRINOX (combination of 5-FU, oxaliplatin, irinotecan, and folinic acid).…”
Section: Discussionmentioning
confidence: 89%
“…We and others have previously shown that hGH action in melanoma upregulates the epithelial-to-mesenchymal transition program ( via upregulation of expression of epithelial-to-mesenchymal transition–related transcription factors) in these cancer cells, thereby promoting their migration and invasion potential ( 45 , 46 , 47 , 48 , 49 , 50 ). Accordingly, the cell migration rate in the absence and presence of hGH was evaluated over a 48-h period including treatments with doxorubicin alone or in conjunction with the candidate GHR antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…Human melanoma cells express a consistently high level of hGHR ( 44 ) and are highly responsive to hGH action, which regulates multiple oncogenic pathways and processes in this cancer ( 45 , 46 , 47 , 48 , 49 , 50 ). Therefore, a GHR antagonist is a candidate negative regulator of melanoma cell growth and therapeutic response.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars from Texas MD Anderson Cancer observed that tumor cells exhibited slower growth and overcame sorafenib resistance by blocking GHR with pegvisomant in vitro ( Kaseb et al, 2022 ). GH inhibition downregulates ABC transporters and sensitizes HCC allografts to sorafenib ( Basu et al, 2022 ). We noted that GHR’s downregulation is associated with HCV-induced HCC ( Lin et al, 2021 ; Abu El-Makarem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%